menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
Which expression is equivalent to 4a +(-6b)-3a+2b
asked
Jul 20, 2019
109k
views
5
votes
Which expression is equivalent to 4a +(-6b)-3a+2b
Mathematics
middle-school
Domenic
asked
by
Domenic
5.6k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
2
Answers
3
votes
4a + (-6b) - 3a + 2b =
= 4a - 6b -3a + 2b
= a - 4b
Maltalef
answered
Jul 22, 2019
by
Maltalef
5.7k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
3
votes
a - 4b
I'm pretty sure
Rob Bajorek
answered
Jul 26, 2019
by
Rob Bajorek
5.5k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
6.2m
questions
8.2m
answers
Other Questions
Solve using square root or factoring method plz help!!!!.....must click on pic to see the whole problem
giles is searching for a sock and discovers that he has 10 socks for every 5 pairs of shoes. if he has 20 socks how many pair of shoes does he have
WILL UPVOTE EVERY ANSWER! MULTIPLE CHOICE! Solve for Y. 8-8y=2y+78 A)y=7 B)y=70 C)y=-7 D)y=-70
What is the solution? −10=2a−4 a=−7 a=−3 a = 3 a = 7
maggie has only dimes and quarters in her purse. she has 27 coins with a total value of 4.05. how many dimes does maggie have in her purse
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org